Back projection algorithm modification for higher probability of moving target detection in SAR data processing - Balaban, M.; Goncharenko, Yu; Gorobets, V.; Kovorotniy, O.; Kivva, F.; Farquharson, G. (Radiofizika i èlektronika, 2020)
Subject and Purpose. The paper is concerned with Synthetic Aperture Radar (SAR) imaging and data processing and seeks to modify the conventional time-domain back projection algorithm (BPA) used for creating a SAR image. The modification consists in the radar squint-angle control at the stage of data processing. Methods and Methodology. Mathematical modeling methods are used. The modeling results are verified by reference to the experimental data. Results. A modification proposed for the back projection algorithm (BPA) enables fast-moving targets to be detected on a stationary image created by synthetic-aperture squint-angle side-looking radar. The back projection algorithm with the squint angle control was experimentally verified by a speedboat example to show that the SAR image has signatures of fast-moving targets which are not observed on the image formed by the classic back projection algorithm. Conclusion. The proposed modification of the back projection algorithm improves the detection probability of fast-moving targets on a SAR image and does it without any complication of the classic back projection algorithm or additional computing time.